Pengaruh Kompres Bawang Merah Plus Virgin Coconut Oil (VCO) Terhadap Penurunan Suhu Tubuh Pasca Imunisasi Difteri Pertusis Tetanus (DPT) - Umbar Sriningsih; Nella Vallen; Qomariyah Qomariyah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
The incidence of fever following DPT (Difteri Pertusis Tetanus) immunisation is relatively high, often necessitating treatment with fever-reducing drugs, which may have adverse effects on infants. Therefore, non-pharmacological methods that are effective, safe, economical, and practical are essential. This research aims to investigate the effectiveness of an onion compress combined with virgin coconut oil (VCO) in reducing body temperature in infants following DPT immunization. The study employed a quasi-experimental method with a one-group pre-test and post-test design. The study population consisted of infants who received DPT immunization in the midwife's independent practice (PMB) working area at the Pudak Payung Health Centre, Semarang, with a total sample size of 48 infants selected via purposive sampling. Data were collected through observation, analysed using descriptive statistics, and the Wilcoxon signed-rank test. Prior to the intervention, 47 infants (45.92%) exhibited fever, and 1 infant (2.08%) had a high fever post-immunisation. Following the application of the shallot compress with VCO, all infants (100%) showed a reduction in body temperature, with none experiencing fever thereafter. The analysis indicated a significant effect of the onion compress combined with VCO on reducing body temperature (Z = -6.042, p < 0.01). The average body temperature of infants post-DPT immunisation decreased from a mean of 38.5°C before the intervention to 37°C afterwards. In conclusion, the use of an onion compress with VCO effectively reduces body temperature in infants following DPT immunization. This non-pharmacological approach presents a promising alternative to conventional fever management strategies.